The Role of Teachers in Instilling The Value Of Honesty Through Civics Learning in Elementary Schools: A Case Study at Sdn 160 Sukalaksana Bandung City - Hidayat, Cecep; Somantri, Mubarok (International Conference on Elementary Education, 2025)
Character education is essential for building children's moral foundations early on, but existing research often focuses on policies, evaluations, or theories, overlooking teachers' everyday classroom practices in fostering values like honesty. This study fills that gap by exploring micro-level pedagogical strategies in daily civics (Pancasila) lessons at an Indonesian elementary school a rarely examinedpractical aspect. Employing a qualitative case study, the research at SDN 160 Sukalaksana, Bandung City, involved three teachers from grades 4-6. Data came from in-depth interviews, extended observations, and document reviews. Key findings highlight three approaches: (1) behavioral modeling, (2) integrating honesty dilemmas into lessons, and (3) habituation via moral reflection. Challengesinclude inconsistent home support and time limitations. This work offers novel insights into feasible